CCR2, CX3CR1, RANTES and SDF1 genetic polymorphisms influence HIV infection in a Zimbabwean pediatric population - Kudakwashe Mhandire; Kerina Duri; Gwendoline Kandawasvika; Precious Chandiwana; Nyasha Chin'ombe; Russell Batsirai Kanyera; Babill Stray-Pedersen; Collet Dandara (Journal of Infection in Developing Countries)
Introduction: There is growing evidence that polymorphisms in chemokine and chemokine receptor genes influence susceptibility to HIV infection and disease progression. However, not much is documented about the prevalence and effects of chemokine and chemokine receptor gene variations in the Zimbabwean population despite the high burden of HIV/AIDS in the country. This study therefore describes polymorphisms in CCR2, CX3CR1, SDF1 and RANTES genes in a Zimbabwean pediatric population and their effects on HIV infection in children born to HIV-infected mothers. Methodology: A total of 106 children between seven and nine years of age comprising 70 perinatally exposed to HIV (34 born infected [EI] and 36 born uninfected [EU]) and 36 unexposed and uninfected (UEUI) controls were recruited. Six allelic variants in four genes were genotyped using PCR-RFLP and sequencing. Results: Frequencies for minor alleles in the HIV uninfected groups (EU and UEUI) were CCR2 190A (16%), SDF1 801A (2%), CX3CR1 745A (9%), CX3CR1 839T (0%), RANTES In 1.1C (20%), and RANTES -403A (44%). There were significant differences between the EI and EU groups in the distribution of CCR2 190G/A genotype (15% versus 39%, respectively, p = 0.02) and CCR2 190G/A-CX3CR1 745G/G genotype combination (0% versus 33%, respectively, p = 0.002). Conclusions: Our findings suggest that chemokine and chemokine receptor gene variants seem to play an important role in the dynamics of HIV infection and could be used as drug or vaccine targets.